Pendampingan Manajemen Waktu Sederhana dalam Membentuk Kebiasaan Disiplin Anak Usia 5-12 Tahun di Desa Kedungrejo, Waru, Sidoarjo - Rizky Aprilia Andinda Putri (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
The development of discipline in children should begin at an early age, particularly in managing time for studying, playing, worship, and resting. Simple time management assistance activities are conducted to help children understand the importance of time regulation and to foster disciplined behavior in their daily activities. These activities include introduction sessions, material delivery, question-and-answer sessions, as well as the distribution of gifts and group photo sessions, all carried out in an interactive and participatory manner. The results indicate that children begin to organize their daily schedules, follow instructions, and demonstrate gradual improvements in discipline. The research method used is Participatory Action Research (PAR), which actively involves children, facilitators, and teachers/ustadzah in the stages of planning, implementation, observation, and reflection. This approach enables children to learn by doing, fostering a sense of responsibility, critical thinking skills, and the development of positive habits in a sustainable manner. The activity is also supported by the active participation of teachers/ustadzah and the facilitation team to enhance the effectiveness of the learning process; therefore, simple time management assistance based on the PAR method is effective in fostering discipline and orderliness in children from an early age.